Immunotactoid glomerulopathy: a case report and literature review - Weerachinchote, Krit; Pichaiwong, Warangkana (Journal of the Nephrology Society of Thailand, 2022)
Immunotactoid glomerulopathy (ITG) is a rare glomerular disease, and 90% of patients are Caucasians. The age of patients with ITG ranges from 50 to 70 years, and the certain pathogenesis remains unknown. The ITG is frequently found with lymphoproliferative disorder and monoclonal gammopathy. Patients with ITG usually present edema, proteinuria, microscopic hematuria, hypertension and renal impairment. The overall course typically progresses to end stage renal disease over several years. The renal outcome of ITG depends on hematologic disease treatment. This report describes a 57-year-old Thai man with a history of hypertension and dyslipidemia presenting generalized edema for 6 months. He had proteinuria, microscopic hematuria, poorly controlled blood pressure and renal impairment. Kidney biopsy was performed, and pathologic features were compatible with immunotactoid glomerulopathy. The additional investigations had not detected any hematologic condition. The standard treatment has not been established, so the previously reported treatment was based on the experience of a nephrologist.